The Dynamic Portrait of Ranunculaceae in Homeopathy: A Materia Medica Perspective (Homoeopathy for All, 2025)
The Ranunculaceae family holds  a distinct position in homeopathy  due to its well-defined symptom  expressions and characteristic  influence on both the mental  and physical planes. This group  is recognized for its heightened  sensitivity, sudden manifestation  of complaints, and alternating  states, which provide a clear  framework for differentiation within  materia medica. In contemporary  practice, where precision and  individualization are highly  valued, the study of Ranunculaceae  remedies remains relevant. By  identifying common patterns while  respecting individual variations,  this family analysis enriches clinical  understanding, supports accurate  remedy selection, and highlights the  enduring importance of botanical  families in homeopathic prescribing.
Keywords: Aconitum napellus; Cimicifuga; Helleborus niger; Vulnerability